PENGARUH KONTEN INFORMASI PENCURIAN TERHADAP PERILAKU FOLLOWERS (STUDI KAUSALITAS AKUN INSTAGRAM @SEMUATENTANGBATAM) - Nadine, Ilovia; ABIDIN, SHOLIHUL (LPPM Universitas Putera Batam, 2023)
One type of new media that is present and becoming viral among users is social media. One of the social media in question is Instagram with the account name @semuatentangbatam. This study aims to determine whether there is an effect of content on the behavior of followers of @semuatentangbatam. If so, how much influence does the theft information content have on the behavior of @semuatentangbatam followers. This study uses a quantitative method with a descriptive approach. The population in this study is followers @semuatentangbatam, namely 201,000 (February 2023). The technique used in sampling in this study was Probability Sampling, namely Simple Random Sampling. The researcher distributed questionnaires to the population sample, namely 399 respondents @semuatentangbatam which were calculated using the Slovin formula. Data analysis techniques used descriptive statistical tests, classical assumption tests, simple linear regression and hypothesis testing. 3. The coefficient test results for the adjusted R-squared value are 0.325838018 or 32.6% while the remaining 67.4% is influenced by other variables. 4. The results of the simple linear regression test with the results of the regression equation Y = 2.168 + 0.445 X1 have a positive value, between the content variable (X) and the behavior variable (Y). Keywords: Behavior; Content; Information; Instagram.